THE PSOCOPTERA OF THE KRAKATAU ISLANDS, INDONESIA - P.J VAUGHAN; LW.B THORNTON; T.R NEW (Treubia, 1989)
At least 80 species of Psocoptera are represented in recent collections from the Krakatau Islands, Sunda Strait. They represent 15 families, and 29 species are described tu new. Twenty four species are known only from the Krahataus but. others are widespread in nearby regions of Sumatra and Java and a few are known to be more broadly distributed. Numbers of species recorded from each of the Krahatau Islands are : Rakata 58, Panjang 48, Sertung 27, Anak Krakatau 27.